Prediksi umur simpan tepung beras ketan berdasarkan isotermi sorpsi air dengan persamaan Guggenheim-Anderson-deBoer - Nikmatul Hidayah; Eka Rahayu (AGROINTEK, 2024)
Acceleration of the shelf life of glutinous rice flour can be determined using the moisture sorption isotherm method with a critical moisture content approach using the Guggenheim-Anderson-deBoer (GAB) model. This research was to determine the prediction of the shelf life of glutinous rice flour in different storage conditions based on moisture sorption isotherm using the GAB model. The stages of the research included determining the parameters of product damage, selecting the packaging, determining the storage condition (temperature 30℃ with humidity of 75%, 85%, and 90%), determining the time and frequency of sampling, data analysis, and prediction of product shelf life. The results showed that the ISA curve of glutinous rice flour had a sigmoid shape (type II). The GAB model accurately described the isotherm sorption characteristics of glutinous rice flour with a Mean Relative Determination of 4.06%. The slope was 0.21 with an R2 value of 0.9835. Generally, the shelf life of glutinous rice flour decreased due to the increasing of storage humidity. The prediction of the shelf life of glutinous rice flour with an initial moisture content of 11.30% and a critical moisture content of 16% with the storage humidity of 75%, 85%, and 90% were 133 days, 71 days dan 56 days, respectively. This research is expected to provide information about the shelf life of glutinous rice flour needed for product distribution and storage purposes.